Lung–kidney interactions in critically ill patients: consensus report of the Acute Disease Quality Initiative (ADQI) 21 Workgroup - Joannidis, Michael; Forni, Lui G.; Klein, Sebastian J.; Honore, Patrick M.; Kashani, Kianoush; Ostermann, Marlies; Prowle, John; Bagshaw, Sean M.; Cantaluppi, Vincenzo; Darmon, Michael; Ding, Xiaoqiang; Fuhrmann, Valentin; et al. (Intensive care medicine, 2020)
Background Multi-organ dysfunction in critical illness is common and frequently involves the lungs and kidneys, often requiring organ support such as invasive mechanical ventilation (IMV), renal replacement therapy (RRT) and/or extracorporeal membrane oxygenation (ECMO). Methods A consensus conference on the spectrum of lung–kidney interactions in critical illness was held under the auspices of the Acute Disease Quality Initiative (ADQI) in Innsbruck, Austria, in June 2018. Through review and critical appraisal of the available evidence, the current state of research, and both clinical and research recommendations were described on the following topics: epidemiology, pathophysiology and strategies to mitigate pulmonary dysfunction among patients with acute kidney injury and/or kidney dysfunction among patients with acute respiratory failure/acute respiratory distress syndrome. Furthermore, emphasis was put on patients receiving organ support (RRT, IMV and/or ECMO) and its impact on lung and kidney function. Conclusion The ADQI 21 conference found significant knowledge gaps about organ crosstalk between lung and kidney and its relevance for critically ill patients. Lung protective ventilation, conservative fluid management and early recognition and treatment of pulmonary infections were the only clinical recommendations with higher quality of evidence. Recommendations for research were formulated, targeting lung–kidney interactions to improve care processes and outcomes in critical illness.